Analisis kemampuan membaca pemahaman dalam menentukan ide pokok pada siswa kelas V sekolah dasar - Pratiwi, Dian Wahyu; Rukayah, Rukayah; Saputri, Dwi Yuniasih (Didaktika Dwija Indria, 2022)
The purpose of this research was to describe the students' reading comprehension ability in class V SDN 01 Karangmojo. This study is a qualitative research with a case study approach. The subjects of this research were 5 fifth grade students of SDN 01 Karangmojo. The subject selection technique is done by criterion based selection. Research data were collected through test data collection techniques, documentation and interviews. This research uses the validity test with the triangulation techniques. The data analysis technique used the Miles and Huberman interactive analysis model. The results showed that the reading comprehension ability of fifth grade students of SDN 01 Karangmojo based on Barrett's taxonomy is literal and reorganization comprehension are the most dominant indicator of reading comprehension ability. This means that students are able to find the meaning of words, determine main ideas, choose important paragraphs, and capture information that is implied in the reading. Low reading comprehension skills are in inferential and evaluative comprehension. Students are quite able to evaluate the content in the reading but have not been able to draw conclusions, assess ideas and express reasons for choosing these ideas.